Organizational aspects of the use of digital marketing tools in the activities of fitness clubs (Physical Culture and Sport: Scientific Perspective, 2023)
The article reveals the organizational and management features of using and implementing Internet marketing in the activities of fitness clubs. The reasons for which it is possible to significantly increase the number of consumers of physical culture and sports services in fitness clubs are revealed, taking into account the current crisis conditions and the variability of the macro environment. The results of the conducted research are presented, which reveal the performance indicators of fitness clubs that require the use of Internet marketing. It was determined that 73.2% of respondents emphasize the use of Internet marketing in the organizational and management activities of fitness clubs, which will contribute to the growth of their image, 71.4% this is an opportunity to objectively evaluate their own professional activity, 65.1% emphasize that , that Internet marketing will orient the work of the fitness club in market conditions and the current state of crisis.The features of using the main methods of web-marketing tools are characterized: search engine optimization (SEO) - audit, usability audit, pay per click (PPC) - analysis, social media marketing (SMM) - analysis, social media optimization (SMO) - analysis, online reputation management (ORM) - audit, end-to-end analytics. Establishing the expediency of using the proposed basic methods of web-marketing tools. According to the results of the analysis of literary sources, the elements of Internet marketing management are defined, not only for fitness clubs, but for any physical culture and sports organization. The expediency of using web-marketing research methods in the professional activity of fitness club employees is revealed
Keywords: fitness club; Internet marketing; web-resources; organizational management activity; macro-environment toolkit